Glatiramer promotes oligodendroglial cell maturation in a cuprizone-induced demyelination model - Rosato Siri, María Victoria (2013)
The therapeutic potential of glatiramer acetate (GA) in Multiple Sclerosis has been apparent for many years and has been proven effective in experimental allergic encephalomyelitis, one of its animal models. The cuprizone (CPZ) model for the CNS de/remyelination has gained a renewed interest during the past decade. CPZ-induced demyelination is considered to be primarily an oligodendrocyte loss with participation of the inflammatory response. As the blood brain barrier remains intact, we found this model advantageous for studying GA effects on CNS remyelination with minimum influence of the peripheral immune cellular component. Our results show that GA, given one week before the CPZ treatment, had a maturational effect functional to remyelination. However, myelin was unorganized as compared to controls. When GA was concomitantly injected with CPZ, oligodendroglial precursor proliferation diminished in favor of maturation and myelin recovered an organized disposition. GA-treated animals also show microglial cell (MG) activation. In vitro assays demonstrated that GA-primed MG cultures had a significant increase in IL-10 and IL-4 secretion. GA-challenged MG-conditioned media induced oligodendrocyte proliferation and subsequent differentiation. Our results suggest that, in addition to its well-recognized immunoregulatory properties, GA also has an effect on resident immuno-response, which leads mature oligodendrocytes towards CPZ-induced demyelination repair.